So into you : [large type] a novel - Fuller, Kathleen (Center Point Large Print, 2025)
"Artist Britt Branch has a successful online channel where she teaches a variety of art lessons. Obsessed with the 1970s, she has a style all her own. But she also has a huge problem -- severe social anxiety. She lives with her mom, and while she pays her own bills, she wonders if she'll ever have the courage to move out and move on. When her best friend announces she's getting married, Britt decides it's time to make a change. Gorgeous Hunter Pickett has always skated by on his model looks, applying very little effort to anything except sports, and even that was iffy at times. The third son of extremely wealthy and successful parents, he dealt with being the black sheep of the family by drinking and using drugs. By his third year of sobriety, he's still dealing with aimlessness. Late one night he catches Britt's channel and ends up watching her videos. He's not interested in art . . . at first. And when he sends her an online message, he's surprised she responds. Before long they are chatting every day, and once they start meeting in person, a spark-filled friendship begins. But both of them are keeping secrets. Big ones. When all truths are revealed in one pivotal moment, Britt and Hunter are at a crossroads. Will he fight for the happiness he's worked so hard to obtain? And will she continue to hide from life, or can she finally step out of her own shadow?"--